A SURVEY OF PLANTS USED IN TRADITIONAL HEALTH REMEDIES OF DOMESTIC ANIMALS BY INDIGENOUS PEOPLE OF SIKKIM, INDIA - Bharati , Kumar Avinash; Sharma , B L (Indian Journal of Veterinary Sciences and Biotechnology, 2009)
In rural Sikkim, where modern veterinary infrastructure is very poor, the local are dependent on their traditional indigenous health care practice to maintain their livestock population. A field survey was done to study and document the indigenous knowledge of various ethnic groups of Sikkim regarding animal healthcare. Number of plants has been collected and the information on their ethnoveterinary uses was gathered from local inhabitants. The information about folk medicinal use, vernacular names of plants and the parts of the plant used are documented. We have recorded 12 sp. of plants, which are used by local people to cure various disease and disorders. The basic aim of the study is to document the knowledge and conserve these medicinal plants.